2021
DOI: 10.1016/j.neo.2021.09.001
|View full text |Cite
|
Sign up to set email alerts
|

In vivo two-photon characterization of tumor-associated macrophages and microglia (TAM/M) and CX3CR1 during different steps of brain metastasis formation from lung cancer

Abstract: Brain metastases frequently occur in lung cancer and dramatically limit prognosis of affected patients. The influence of tumor-associated macrophages and microglia (TAM/M) and their receptor CX3CR1 on different steps of brain metastasis formation from lung cancer is poorly characterized. We established a syngeneic orthotopic cerebral metastasis model in mice by combining a chronic cranial window with repetitive intravital 2-photon laser scanning microscopy. This allowed in vivo tracking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…In BM, the proportion of most immune cell subpopulations decreases, but with a few exceptions, such as M2-macrophages, whose ratio in the proportion is strongly associated with BM ( 65 ). Therefore, the change of TAM/m from M1 to M2 phenotype may be one of the reasons for the shift of TME from anti-tumor to pro-tumor ( 66 ). Recent in-depth studies of lung cancer BM have revealed that around 10% of TAM/m contain peripheral-derived macrophages in early metastases, rising to 20% in massive metastases ( 67 ).…”
Section: Tme and Immunotherapy Of Bm From Nsclcmentioning
confidence: 99%
See 3 more Smart Citations
“…In BM, the proportion of most immune cell subpopulations decreases, but with a few exceptions, such as M2-macrophages, whose ratio in the proportion is strongly associated with BM ( 65 ). Therefore, the change of TAM/m from M1 to M2 phenotype may be one of the reasons for the shift of TME from anti-tumor to pro-tumor ( 66 ). Recent in-depth studies of lung cancer BM have revealed that around 10% of TAM/m contain peripheral-derived macrophages in early metastases, rising to 20% in massive metastases ( 67 ).…”
Section: Tme and Immunotherapy Of Bm From Nsclcmentioning
confidence: 99%
“…In contrast to primary NSCLC, BM microenvironment macrophages infiltrate more and show elevated monocyte-derived macrophages ( 47 ). The phenomena may reflect the antitumor effect of TAM/m in the early stages of BM formation and the accumulation and activation of TAM/m in the later stages ( 66 ).…”
Section: Tme and Immunotherapy Of Bm From Nsclcmentioning
confidence: 99%
See 2 more Smart Citations
“…The next step to perform a MP-IVM protocol is to select the proper surgical model, to enable the exposure and immobilization of the targeted organ (Figure 1A) (8,9,55). Although this typically requires minimally invasive surgery, more advanced surgical setups can be employed for long-term imaging of internal organs, including gut (56), brain and spinal cord (57), primary tumors and metastasis (58,59) amongst others (60)(61)(62)(63).…”
Section: Surgerymentioning
confidence: 99%